2018
DOI: 10.18632/oncotarget.24587
|View full text |Cite
|
Sign up to set email alerts
|

A porcine placental extract prevents steatohepatitis by suppressing activation of macrophages and stellate cells in mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is caused by ectopic fat accumulation in the liver. NAFLD is associated with hepatic inflammation and oxidative stress, resulting in nonalcoholic steatohepatitis (NASH) with advanced fibrosis. Placental extracts have been used to treat various chronic diseases due to their antioxidative effect. However, the effects of the extracts on the development of NASH have yet to be elucidated. Here, we demonstrated that supplementation with an oral porcine placental extract (PPE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…On the contrary, M2‐polarized macrophages secreted anti‐inflammatory cytokines and later contributed to the maintenance of insulin sensitivity . Coincident with previous data , our results showed increased obesity‐induced inflammation, M1‐type polarization of macrophages, and compromised insulin activities in WT mice exposed to an HFD for 12 weeks. In contrast, VWF −/− mice displayed decreased obesity‐induced inflammation and M1‐type polarization of macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, M2‐polarized macrophages secreted anti‐inflammatory cytokines and later contributed to the maintenance of insulin sensitivity . Coincident with previous data , our results showed increased obesity‐induced inflammation, M1‐type polarization of macrophages, and compromised insulin activities in WT mice exposed to an HFD for 12 weeks. In contrast, VWF −/− mice displayed decreased obesity‐induced inflammation and M1‐type polarization of macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…Given the ability of IL-23 to promote the secretion of IL-10 and regulate IL-17 production by CD4 + T cells [ 42 ], one may propose that the administration of human placental extract in the first place, may suppress the destructive activity of autoreactive T cells in EAE. Similarly, human placental extract can suppress the secretion of several pro-inflammatory mediators, including IL-23 and several other mediators mentioned in different studies, resulting in the attenuation of inflammation and the mean clinical score in EAE mice [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The porcine placental extract (PPE) used in this study was produced by Snowden (Tokyo) using a combination of fermentation and proteolysis as previously described [27]. Briefly, the porcine placenta was obtained as afterbirth and was fermented with yeast ( Zygosaccharomyces sp.)…”
Section: Methodsmentioning
confidence: 99%
“…Since the placenta contains various nutrients including amino acids, nucleic acids, minerals, vitamins, hormones and some growth factors, it has been used in traditional medicines for fatigue, menopausal symptoms, skin whitening and antiaging from ancient times to the present [2126]. Recent studies, in fact, have demonstrated that a hydrolyzed extract of the placenta, known simply as “placental extract”, has beneficial effects such as amelioration of non-alcoholic steatohepatitis (NASH) and other forms of liver regeneration, increased proliferation of skin fibroblasts and marrow cells, and anti-inflammatory and anti-oxidant activities [2730]. In the present study, we examined the broad spectrum of effects of placental extract, with a focus on the influence of placental extract on adipogenesis.…”
Section: Introductionmentioning
confidence: 99%